Exploring Shared Leadership : Mediating Roles of Spirit at Work and Team Trust - Prabhu, Nandan; Koodamara, Navin Kumar (Prabandhan: Indian Journal of Management, 2022)
This paper aimed to develop a model of serial mediation in team effectiveness. We adopted the theory-building approach to identify the gaps in the relationship among relevant variables of the study to build a serial mediation model. We conceptualized a serial mediation model in which the constructs of ‘spirit at work’ and ‘team trust’ were posited as mediators in the relationship between shared transformational leadership and team effectiveness. This paper provided theoretical premises among the study constructs by drawing on robust theories such as symbolic interactionist theories of identity, comprehensive workplace spirituality facilitation model, and individuation theory. This paper calls for the conceptualization of multidimensional constructs such as shared transformational leadership and spirit at work as reflective – formative constructs, instead of their conceptualization as reflective – reflective constructs, as the scholars theorize the direction of causality to flow from dimensions to the latent construct.